2019
DOI: 10.3389/fspor.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Muscle Deoxygenation vs. Sustained High VO2 During High-Intensity Interval Training in Sprint Canoe-Kayak

Abstract: Recent data suggests that peripheral adaptations, i.e., the muscle ability to extract and use oxygen, may be a stronger predictor of canoe-kayak sprint performance compared to VO 2 max or central adaptations. If maximizing the time near VO 2 max during high-intensity interval training (HIIT) sessions is believed to optimize central adaptations, maximizing the time near maximal levels of muscle desaturation could represent a critical stimulus to optimize peripheral adaptations.Purpose: Therefore, the purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…SIT, however, has been shown to improve endurance performance in trained cyclists (Laursen et al, 2002 ) and runners (Esfarjani and Laursen, 2007 ). Although time spent at >90% VO 2 max during SIT sessions is low (typically 0–60 s in trained cyclists for an entire training session), it has been suggested that muscle O 2 demand is high, especially as the number of sprints increases, as suggested by low muscle oxygenation levels (Buchheit et al, 2012 ; Paquette et al, 2019 ). In the present study, both groups increased the peak power output during the Wingate test, but only the chronic application of bilateral IPC prior to SIT sessions improved TT performance in endurance athletes in just 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…SIT, however, has been shown to improve endurance performance in trained cyclists (Laursen et al, 2002 ) and runners (Esfarjani and Laursen, 2007 ). Although time spent at >90% VO 2 max during SIT sessions is low (typically 0–60 s in trained cyclists for an entire training session), it has been suggested that muscle O 2 demand is high, especially as the number of sprints increases, as suggested by low muscle oxygenation levels (Buchheit et al, 2012 ; Paquette et al, 2019 ). In the present study, both groups increased the peak power output during the Wingate test, but only the chronic application of bilateral IPC prior to SIT sessions improved TT performance in endurance athletes in just 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered one of the most effective strategies for enhancing performance in athletes. This kind of training consists of alternating short bouts (10–30 s) of high-intensity exercise (>85–90% VO 2max ) interspersed with recovery periods [ 1 , 2 ] Repeated-sprint training (RST) is critical to improving endurance and performance in high-intensity exercise through peripheral muscular adaptations [ 3 ]. In this sense, RST has been one of the most important fitness indicators and has been widely studied [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies highlight the importance of peripheral adaptations for kayak performance, particularly in the sport-specific training period. Acute and specific changes in muscle oxygenation during various high-intensity interval training sessions suggest that some of the sessions typically performed by kayakers have the potential to induce peripheral adaptations (Paquette et al, 2019 ). However, to our best knowledge, training-induced chronic changes in muscle oxygenation parameters have not been assessed in kayak.…”
Section: Introductionmentioning
confidence: 99%